Mounting an immune response correlates with decreased androgen levels in male peafowl, Pavo cristatus - Ros, Albert F. H. (2009)
Studies testing the ‘‘immunocompetence handicap hypothesis’’ have focussed on the immunosuppressive effects of androgens. Several recent studies have reported that mounting a humoral immune response might also result in a decrease in circulating androgen levels via a ‘‘negative feedback’’ on the hypothalamus–pituitary– gonadal axis (HPG). The aim of this correlative study was to analyse these immunosuppressive and HPG-suppressive interactions in reproductively active males of the peafowl. We collected blood samples of free living birds before and after challenging the immune system with a non-pathogenic antigen (sheep erythrocytes), and analysed immune parameters and plasma levels of the two main androgens in birds, testosterone and dihydrotestosterone. Males displaying larger versions of the main secondary sexual trait, the long and conspicuously ornamented train, tended to have higher androgen levels and significantly lower circulating levels of leukocytes, indicating that exaggerated ornaments might signal properties of the endocrine and immune system. Actual circulating levels of androgens did not correlate with the plasma levels of leukocytes and the antibody response to SRBC. However, changes in plasma levels of both androgens showed negative correlation with both leukocytes (P\0.1) and SRBC responses (P\0.05). The data therefore support the prediction that activity of the immune system is HPG-suppressive. Such suppression has been proposed to be especially costly during the reproductive season, during which androgens facilitate the expression of exaggerated traits that play an important role in sexual competition.